2021
DOI: 10.15585/mmwr.mm7024a3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Among Parents of Children Aged <18 Years and Unpaid Caregivers of Adults During the COVID-19 Pandemic — United States, December 2020 and February–⁠March 2021

Abstract: Early during the COVID-19 pandemic, nearly two thirds of unpaid caregivers of adults reported adverse mental or behavioral health symptoms, compared with approximately one third of noncaregivers † (1). In addition, 27% of parents of children aged <18 years reported that their mental health had worsened during the pandemic (2). To examine mental health during the COVID-19 pandemic among U.S. adults on the basis of their classification as having a parenting role (i.e., unpaid persons caring for children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…[ 17 ] and by Czeisler and coll. [ 16 ] that have shown a deterioration in parents’ psychological well-being due to COVID-19 pandemic, which significantly affected children’s psychological well-being through the resulting increase of parenting stress levels [ 5 , 29 , 53 ]. In this field, clinicians and researchers rooted in the Developmental Psychopathological framework have widely suggested that parental psychopathological difficulties may affect children’s emotional-adaptive functioning in a cascading way [ 64 ], from the transmission of predisposition to (epi-)genetic vulnerabilities [ 65 , 66 ], to children’s exposure to an adverse affective family environment [ 67 , 68 , 69 ], including poor quality of parent-child interactions [ 30 , 70 , 71 ], family functioning [ 72 , 73 , 74 , 75 ], and high parenting stress levels [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 17 ] and by Czeisler and coll. [ 16 ] that have shown a deterioration in parents’ psychological well-being due to COVID-19 pandemic, which significantly affected children’s psychological well-being through the resulting increase of parenting stress levels [ 5 , 29 , 53 ]. In this field, clinicians and researchers rooted in the Developmental Psychopathological framework have widely suggested that parental psychopathological difficulties may affect children’s emotional-adaptive functioning in a cascading way [ 64 ], from the transmission of predisposition to (epi-)genetic vulnerabilities [ 65 , 66 ], to children’s exposure to an adverse affective family environment [ 67 , 68 , 69 ], including poor quality of parent-child interactions [ 30 , 70 , 71 ], family functioning [ 72 , 73 , 74 , 75 ], and high parenting stress levels [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some families have shown adaptive responses to the adverse circumstances imposed by the COVID-19 preventive strategies [ 13 ], maintaining a positive involvement with family members and the extra-family social network [ 14 , 15 ], and experiencing a sense of self-efficacy [ 2 ]. Nevertheless, national and international research reported that a large part of families of the general population experienced the pandemic as a traumatic event, manifesting anxiety, depression [ 16 ], and peritraumatic distress symptoms [ 17 , 18 ]. In this context, the few studies conducted during the so-called “second wave” of COVID-19 have confirmed the long-term effects on mental health and increased psychopathological symptoms as the pandemic continues [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as more longitudinal studies emerge, it is apparent that mental health impact may vary and evolve among older adults depending on their individual circumstances. Longitudinal data are sharpening our understanding of the long-term effects of COVID among recoverees 8 , long COVID 9 , the impact of physical and social distancing 10 and the disproportionate impact on the health of people with dementia and especially their caregivers 11 , 12 , 13 .…”
mentioning
confidence: 99%